Pengaruh pemberian ekstrak gulma Imperata cylindrica terhadap pertumbuhan gulma elusine indica dan tanaman jagung (Zea mays L.) - Aditya Murtilaksono; Asrun Asrun; Alisa Nurhafida (JURNAL AGRONIDA, 2025)
Eleusine indica is a dominant weed species commonly found in maize fields and can significantly suppress maize growth. The use of plant-based herbicides derived from Imperata cylindrica offers an alternative strategy for controlling E. indica. Such herbicides are considered environmentally friendly because they originate from organic materials. This study aimed to evaluate the effects of I. cylindrica weed extract on the growth of E. indica and maize plants. The experiment was conducted using a randomized complete block-design with a single factor, namely I. cylindrica extract concentration. Treatments consisted of a control (without I. cylindrica extract) and extract concentrations of 20%, 40%, 60%, 80%, and 100%. Observed variables included maize plant height, number of leaves, shoot fresh and dry weights, root fresh and dry weights, weight of husked maize ears, as well as the height, number, fresh weight, and dry weight of E. indica. Data were analyzed using analysis of variance (ANOVA), and treatments showing significant effects were further analyzed using Duncan’s Multiple Range Test (DMRT). The results showed that application of 100% I. cylindrica extract resulted in significantly lower maize plant height and a significantly reduced number of leaves compared to other treatments, except for the 80% concentration. The 100% extract treatment suppressed E. indica height by up to 10.17% and reduced the number of E. indica leaves by up to 12.5% at 2 weeks after planting. These findings indicate the potential of Imperata cylindrica as an environmentally friendly plant-based herbicide without adversely affecting the main crop.